A review of hydrogen production through solar energy with various energy storage devices - Liu, Zhengguang; Xie, Jinliang; Song, Chenchen; Yang, Xiaohu; Kalogirou, Soteris A. (My University, 2025)
The importance of solar energy and hydrogen lies in their provision of clean, renewable solutions for sustainable energy. Solar hydrogen production has attracted widespread attention due to its cleanliness, safety, and potential climate mitigation effects. This is the first paper that reviews various solar hydrogen production methods including solar electrolysis, solar chemical, and solar biohydrogen and their nexus with various energy storage devices. An analysis of published papers shows that solar electrolysis centralized systems face challenges in land use and infrastructure costs, but distributed systems were experiencing higher unit costs and complex maintenance. Another method, solar thermochemical production, can achieve high efficiencies but is challenged by material stability and cost. Photocatalytic and photoelectrochemical methods were constrained by factors like light absorption and system complexity. Photosynthetic organisms need innovations in genetic engineering and bioreactor design. Further to the problems outlined above, this paper gives various benefits of energy storage solutions, and their optimal construction matching was made according to the characteristics of the equipment. Despite its generally low efficiency, heat storage could be advantageous in regions with limited sunlight, providing unique benefits in cold areas. Finally, the article shows possible future research directions and perspective, which will undoubtedly be of great significance for future sustainable development goals.
Keywords: Energy storage; Hydrogen; Photovoltaic-electrolysis; Solar energy; Solar-hydrogen nexus